Protein Composition of Circulating Extracellular Vesicles Immediately Changed by Particular Short Time of High-Intensity Interval Training Exercise - Kobayashi, Yoshinao; Eguchi, Akiko; Tamai, Yasuyuki; Fukuda, Sanae; Tempaku, Mina; Izuoka, Kiyora; Iwasa, Motoh; Takei, Yoshiyuki; Togashi, Kenji (Frontiers in Physiology, 2021)
[Introduction/Purpose] High intensity interval training (HIIT) promotes various biological processes and metabolic effects in multiple organs, but the role of extracellular vesicles (EVs) released from variety of cells is not fully understood during HIIT exercise (HIIT-Ex). We investigated the changes in circulating number and proteomic profile of EVs to assess the effect of HIIT-Ex. [Methods] Seventeen young men (median age, 20 y) enrolled in the study. Total duration of the HIIT-Ex was 4 min. Blood samples were collected from before HIIT-Ex (pre-HIIT-Ex), at the immediate conclusion of HIIT-Ex (T0), at 30 min (T30), and at 120 min after HIIT-Ex. The pulse rate and systolic blood pressure were measured. Circulating EVs were characterized and EV proteins were detected via nano liquid chromatography tandem-mass spectrometry. [Results] The pulse rate and systolic blood pressure at T0 to pre-HIIT-Ex were significantly higher. Circulating EV number was significantly altered throughout the HIIT-Ex and the source of circulating EVs included skeletal muscle, hepatocytes, and adipose tissue. Proteomic analysis identified total 558 proteins within isolated circulating EVs from pre-HIIT-Ex, T0, and T30. Twenty proteins in total were significantly changed among at pre-HIIT-Ex, T0 and T30 and are involved in a variety of pathways, such as activation of coagulation cascades, cellular oxidant detoxification, and correction of acid-base imbalance. Catalase and peroxiredoxin II were increased at T0. [Conclusion] The circulating EV composition can be immediately changed by particular short time of HIIT-Ex, indicating that EVs may intercommunicate across various organs rapidly in response to HIIT-Ex.